Ferrite plastic magnetic material with high powder filling rate as well as preparation method and application of ferrite plastic magnetic material
By using a specific additive system in ferrite plastic magnetic materials with high powder filling rate, the problem of poor fluidity and mechanical properties of ferrite injection molded materials is solved, and the balanced magnetic properties and mechanical properties are improved.
Patent Information
- Application Number
- CN202411782238.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-25
AI Technical Summary
Under high powder filling rate, the fluidity and mechanical properties of the ferrite injection molding materials are poor, resulting in difficulty in forming, fluctuations in magnetic properties and mechanical properties. The compatibility of the ferrite/PA6 plastic magnetic system with adhesive components or additive additives is poor, which is prone to group analysis, frost, and scaling problems.
Ferrite plastic magnetic material with high powder filling rate is used, including ferrite magnetic powder, PA6 and additives, which include the first lubricating component, the second lubricating component, the compatible component and the nucleating component. Through the combination of these additives, the compatibility and flowability of the magnetic powder and PA6 are improved, and the molding and mechanical properties are improved.
It has achieved excellent performance in taking into account both magnetic properties, processing properties and mechanical properties under high powder filling rate conditions, with 20% improvement in fluidity, good magnetic field orientation, high surface magnetic strength, and physical performance such as good impact strength and high tensile strength.
Smart Images

Figure BDA0005173055920000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of plastic magnetic materials, and in particular to a ferrite plastic magnetic material with a high powder filling rate, a preparation method and an application thereof. Background Art
[0002] Ferrite plastic magnetic material is a kind of injection molding granules obtained by uniformly mixing oxides of iron and other metals, binders, lubricants, etc. at a certain ratio at high speed, heating and mixing in a twin-screw extruder, and cooling and pelletizing. The ferrite injection molding granules are melted at a certain temperature and injected into the mold cavity, and then cooled and shaped under the action of a magnetic field before being ejected from the mold. They can be processed into plastic magnetic products of specified shapes and sizes, such as plastic magnetic rotors, multi-pole magnetic rings, etc. Compared with sintered permanent magnetic materials, plastic magnetic materials have the characteristics of one-time injection molding with shafts, good consistency, high precision, and easy multi-pole production. They can be made into complex-shaped multi-pole oriented magnets and thin-walled products, which can be assembled in micro motors and are widely used in variable-frequency home appliances, office equipment, high-end automobiles and other fields.
[0003] In ferrite plastic magnetic materials, oxides of iron and other metals can be called magnetic powder, which is the key component to produce magnetism in ferrite plastic magnetic materials. The proportion of magnetic powder directly affects the magnetic performance of plastic magnetic materials. When the proportion of magnetic powder is higher, the magnetic performance indicators of ferrite such as remanence and magnetic energy product are significantly improved; however, it will also lead to disadvantages such as poor processing fluidity, difficult molding, uneven distribution of magnetic powder leading to fluctuations in magnetic properties, easy demagnetization, and low mechanical strength. Therefore, based on the overall performance and use effect, the filling rate of magnetic powder in existing plastic magnetic materials is controlled at ≤90wt.%.
[0004] However, with the development of social intelligence, micro motors are updated and iterated, requiring smaller and smaller volumes, and products tend to develop towards high performance, miniaturization, and lightweight. Therefore, injection molding granules, as the key raw material for the plastic magnetic rotor of micro motors, require higher magnetic properties; when producing the same magnetic flux density, the volume of the magnet will decrease, which is in line with the future development trend of the product. Therefore, a higher powder filling rate is required to meet the development needs of industries such as micro motors.
[0005] On the other hand, the flowability of injection molding granules is also a very critical technical indicator in injection molding. Injection molding granules are semi-finished products in the intermediate link of the production of plastic magnetic material products. During the extrusion granulation and injection molding process, the polymer usually has a higher viscosity after melting. When passing through narrow slits, gates and other runners, the polymer melt must produce friction with the surface of the processing machinery. When the fluidity is too low, a higher propulsion pressure is required, which is easy to damage the equipment, and there are defects such as reduced surface magnetic flux, insufficient mold filling, and rough surface; on the contrary, too high fluidity will affect the mechanical properties of the material, resulting in material overflow, brittle products, and even cracking. When the powder filling rate is high, the interaction between the filler particles is enhanced, the orientation resistance of the magnetic powder in the magnetic field increases, the viscosity of the system increases, and the fluidity decreases. Generally, the fluidity of ferrite powder is much lower than that of binder. Therefore, too high a filling amount of magnetic powder will increase the viscosity of the plastic-magnetic mixture system and deteriorate the fluidity (MFR), which often causes an increase in injection molding pressure and makes magnet molding difficult. The rotation of magnetic powder particles is restricted, resulting in a low degree of orientation and a decrease in magnetic flux. The processing characteristics are reduced, leading to many problems such as rough magnet surface, pores or voids inside, which in turn affects the processing and molding quality of the product.
[0006] Furthermore, when the filling rate of magnetic powder is controlled to be greater than 90wt.%, and conventional binders such as PA6 (polyamide 6), PA12 (polyamide 12) and PPS (polyphenylene sulfide) are used, the mechanical properties of the plastic magnetic product will be greatly reduced due to the lack of binder, resulting in a strong internal stress concentration effect inside the plastic magnetic product, causing the plastic magnetic material to be prone to cracking and deformation during the injection molding process, and after being made into plastic magnetic products (such as plastic magnetic rotors and magnetic rings), they are also prone to cracking and deformation during use (such as high-speed rotation), resulting in low yields, limiting its application in certain high-end fields or extreme conditions. Therefore, the current conventional functional additive system does not support such a high filling rate of magnetic powder.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The first purpose of the present invention is to provide a ferrite plastic magnetic material with a high powder filling rate, which is mainly used to solve the defects of poor fluidity and mechanical properties of ferrite injection molding materials at high powder filling rates, and the problem of being unable to be molded or deforming and cracking; on the other hand, it is used to solve the poor compatibility of the ferrite / PA6 plastic magnetic system with adhesive components or additive additives, and the defects of component separation, frosting and scaling.
[0009] The second object of the present invention is to provide a method for preparing the ferrite plastic magnetic material with a high powder filling rate.
[0010] A third object of the present invention is to provide a magnetic product.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] A ferrite plastic magnetic material with a high powder filling rate, comprising ferrite magnetic powder, PA6 and an additive; the additive comprises a first lubricating component, a second lubricating component, a compatible component and a nucleating component;
[0013] Wherein, the mass proportion of the ferrite magnetic powder is ≥91%;
[0014] The first lubricating component includes at least one of erucamide or oleamide;
[0015] The second lubricating component includes ethylene bisstearamide;
[0016] The compatible component comprises at least one of hydrogenated styrene-butadiene block copolymer grafted with maleic anhydride, hydrogenated styrene-butadiene block copolymer grafted with glycidyl methacrylate, polyolefin elastomer grafted with maleic anhydride, and polyolefin elastomer grafted with glycidyl methacrylate;
[0017] The nucleating component includes calcium montanate.
[0018] A method for preparing the ferrite plastic magnetic material comprises the following steps:
[0019] The ferrite powder, PA6 and additives are mixed until uniform, and then extruded into granules, and after cooling, injection molded in a magnetic field to obtain a plastic magnetic material.
[0020] A magnetic product comprises the ferrite plastic magnetic material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a ferrite / PA6 plastic magnetic material with a high powder filling rate. By limiting its formula and ratio, it can achieve excellent performance in magnetic properties, processing properties, mechanical properties and other aspects. The PA6 and additives used in the present invention are generally applicable to any ferrite magnetic powder; compared with conventional ferrite / PA6 plastic magnetic materials, the flowability is improved by at least 20%, and it has magnetic properties such as good magnetic field orientation and high surface magnetic strength, as well as physical properties such as good impact strength and high tensile strength. It is worth noting that due to the significant increase in the content of magnetic powder in the present invention, the magnetic properties of the ferrite / PA6 plastic magnetic material reach the Toda TP-S69H standard, which is also the highest magnetic property level of ferrite / PA6 plastic magnetic materials that can be mass-produced at present. DETAILED DESCRIPTION
[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "first", "second" and "third" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.
[0024] The first aspect of the present invention is to provide a ferrite plastic magnetic material with a high powder filling rate.
[0025] It should be emphasized that the "high powder filling rate" mentioned in the present invention means that the mass proportion of ferrite magnetic powder in the ferrite plastic magnetic material is ≥ 91% (the total mass of the ferrite plastic magnetic material is 100%). In the currently common ferrite plastic magnetic materials or products, the magnetic powder content is usually ≤ 90wt.%, which is also a process selection based on the control of overall properties such as mechanical properties and flow properties. However, in the face of the increasing requirements for magnetic properties in the plastic magnetic industry, a higher powder filling rate is the general trend of technological development.
[0026] The ferrite plastic magnetic material with high powder filling rate comprises ferrite magnetic powder, PA6 and additives; the additives comprise a first lubricating component, a second lubricating component, a compatible component and a nucleating component.
[0027] As a preferred embodiment, the ferrite magnetic powder includes ferric oxide (Fe2O3), and optionally includes one or more other metal oxides or metal salts, including but not limited to strontium oxide, barium oxide, cobalt oxide, nickel oxide, zinc oxide, copper oxide, barium carbonate, strontium carbonate, manganese oxide, magnesium oxide, etc.
[0028] As a preferred implementation, the particle size of the ferrite magnetic powder is 1.6 μm to 1.9 μm.
[0029] In the present invention, the differences in processing performance or mechanical properties between different ferrite powders are negligible, and the bonding and auxiliary agent system designed in the present invention is universal for the ferrite powders. Therefore, the present invention does not impose any restrictions on the specific composition of the ferrite powders, and those skilled in the art can select any conventional or unconventional ferrite powder and adapt it to the technical solution of the present invention.
[0030] As a preferred embodiment, the PA6 is polyamide 6, which is a polymer compound polymerized from caprolactam; the PA6 of the present invention includes one or more of the following features:
[0031] (a) The molecular weight of the PA6 is 15,000 to 30,000, including but not limited to any one of 1.5, 1.6, 1.8, 2.0, 2.2, 2.4, 2.5, 2.6, 2.8, 3 (ten thousand) or any two thereof;
[0032] (b) the relative viscosity of the PA6 is 1.80-2.45, including but not limited to any one of 1.80, 1.85, 1.90, 1.95, 2.00, 2.10, 2.20, 2.30, 2.40, 2.45 or a numerical range consisting of any two thereof;
[0033] (c) The melting point of the PA6 is 210°C to 230°C, including but not limited to any one of 210, 215, 220, 225, 230 (°C) or a numerical range consisting of any two thereof; the heat deformation temperature of the PA6 is 50°C to 80°C, including but not limited to any one of 50, 55, 60, 65, 70, 75, 80 (°C) or a numerical range consisting of any two thereof;
[0034] (d) The density of PA6 is 1.10 g / cm 3 ~1.18g / cm 3 , the moisture content of PA6 is ≤0.15%.
[0035] It is worth noting that, in order to improve the impact toughness and tensile strength of ferrite plastic magnetic materials, medium and high viscosity nylon products are usually directly added, such as Xinhui Meida M2400, Hunan Yuehua YH400, Japan Ube 1013, 1015, 7024B, etc. However, correspondingly, the addition of such additives will greatly reduce the flow properties of the material and greatly affect the processing performance. The present invention can solve the problem defects under the condition of high powder filling rate by combining the PA6 with the above characteristics and the auxiliary agent system.
[0036] In the present invention, the first lubricating component comprises at least one of erucic acid amide or oleic acid amide. In the present invention, the second lubricating component comprises ethylene bisstearamide.
[0037] The main function of the lubrication system composed of two lubricating components in the present invention is to reduce the friction and loss between the polymer and the processing equipment, and between the polymer and the auxiliary component, and increase the overall fluidity of the material during the processing. By using two lubricating components to work together and synergistically lubricate from the inside and outside dimensions of the plastic magnetic material, the material flow performance is greatly improved, and the defects such as dissatisfaction of injection molding, poor magnetic field orientation, and low surface magnetic strength caused by low fluidity are solved. In addition to improving fluidity, it also promotes melting, facilitates demolding, and prevents adhesion.
[0038] In the present invention, the compatible component includes at least one of hydrogenated styrene-butadiene block copolymer grafted with maleic anhydride (SEBS-g-MAH), hydrogenated styrene-butadiene block copolymer grafted with glycidyl methacrylate (SEBS-g-GMA), polyolefin elastomer grafted with maleic anhydride (POE-g-MAH), and polyolefin elastomer grafted with glycidyl methacrylate (POE-g-GMA).
[0039] As a preferred embodiment, the molecular weight of the compatible component is 70,000 to 150,000, including but not limited to any one of 7, 8, 9, 10, 11, 12, 13, 14, and 15 (ten thousand) or a numerical range consisting of any two of them.
[0040] The present invention achieves the improvement of compatibility of magnetic powder, PA6 and other polymer auxiliary components, promotes uniformity of dispersed phase, and improves adhesion of interface by adding the compatible component. It can be understood that for the blending system, compatibility between components is the key to polymer blending modification; magnetic powder and PA6 in the art are two materials with completely different properties. Magnetic powder is a hydrophilic and oleophobic inorganic compound, while PA6 is an oleophilic and hydrophobic organic substance with a strong polar amide group. When blended with non-polar magnetic powder or weak polar polymer, the compatibility between the two phases is poor, the phase separation phenomenon is serious, and the performance of the blend is reduced.
[0041] In the present invention, by introducing specific compatible components and mixing and melting in the preparation process, the prepared graft copolymer has anhydride functional groups or glycidyl methacrylate functional groups, which are easy to react with the terminal amino group of PA6 to form chemical bonds; further, due to the formation of chemical bonds at the interface, the interfacial energy between the two phases of magnetic powder, PA6, lubricating components, etc. is effectively reduced, the agglomeration of the dispersed phase is prevented and the dispersion of the phase is promoted, the bonding between the two phases is strengthened, the particle size of the dispersed phase in the system becomes smaller and the dispersion is uniform, thereby achieving a significant effect of improving compatibility.
[0042] In the present invention, the nucleating component includes calcium montanate.
[0043] The present invention provides crystal nuclei in a molten state by adding the nucleating component, so that the polymer changes from original homogeneous nucleation to heterogeneous nucleation, thereby accelerating the crystallization speed and forming smaller spherulites, refining the grain structure, and being beneficial to improving the transparency, rigidity, surface gloss, impact toughness and thermal deformation temperature of the plastic magnetic product, thereby effectively shortening its molding cycle; in addition, since crystallization begins at a higher temperature, it is helpful to enhance the flow and demoulding properties, and thus it also has certain functions of a flow promoter and a demoulding agent.
[0044] As a preferred embodiment, the ferrite plastic magnetic material includes the following components by mass: 1000 parts of ferrite magnetic powder, 75-120 parts of PA6, 3-20 parts of a first lubricating component, 2-15 parts of a second lubricating component, 0.5-10 parts of a compatible component and 0.1-5 parts of a nucleating component; in some more preferred embodiments, the component ratio can be: 1000 parts of ferrite magnetic powder, 80-90 parts of PA6, 5-15 parts of a first lubricating component, 2-8 parts of a second lubricating component, 1-5 parts of a compatible component and 0.1-2 parts of a nucleating component.
[0045] As an optional embodiment, the mass fraction of each component includes but is not limited to the point values listed below, or the numerical range formed by any two of the listed point values: PA680, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90; the first lubricating component 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15; the second lubricating component 2, 3, 4, 5, 6, 7, 8; the compatible component 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5; the nucleating component 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 2; the above values are dimensionless and are weight fractions.
[0046] As a more preferred embodiment, the content of the nucleating component is 0.2 wt.% to 0.5 wt.%.
[0047] As a preferred embodiment, the ferrite plastic magnetic material also includes an antioxidant; in some optional embodiments, the antioxidant includes one or more of a hindered phenol antioxidant, a phosphite antioxidant or an aromatic amine antioxidant, and the reference amount of the antioxidant is 0.1 to 1 part based on the above-mentioned mass fraction.
[0048] As a preferred embodiment, the ferrite plastic magnetic material also includes a coupling agent; in some optional embodiments, the coupling agent includes at least one of a silane coupling agent or a titanate coupling agent, and the reference amount of the antioxidant is 0.1 to 2 parts by mass.
[0049] The second aspect of the present invention is to provide a method for preparing the ferrite plastic magnetic material with a high powder filling rate as described in the first aspect.
[0050] The preparation method comprises the following steps: mixing ferrite magnetic powder, PA6 and an auxiliary agent until uniform, then extruding and granulating, and injection molding in a magnetic field after cooling to obtain a plastic magnetic material.
[0051] As a preferred embodiment, the PA6 is dried before the preparation method; because PA6 is a polymer material that easily absorbs water, it is easy to cause problems such as material deformation and strength reduction, and PA6 needs to be dried before processing; as a more preferred embodiment, the drying temperature is 80°C to 120°C, and the drying time is 12h to 20h.
[0052] As a preferred embodiment, the preparation method comprises the following steps: mixing PA6 and an additive until uniform, extruding and obtaining a mixed material (the mixed material is preferably in a granular form); mixing the ferrite magnetic powder and the mixed material again until uniform; then extruding and granulating, and after cooling, injection molding in a magnetic field to obtain a plastic magnetic material.
[0053] As a preferred embodiment, the granulation temperature is 200°C to 260°C, and the granulation time is 4min to 12min; as a more preferred embodiment, the granulation parameters include: the feed port temperature is 180°C to 210°C, the discharge port temperature is 210°C to 240°C, the rotation speed is 10% to 60% Max, the pressure is 0.3MPa to 1.6MPa, and the torque is 10% to 60%.
[0054] As a preferred embodiment, the particle size of the granules obtained by granulation is 1 mm to 5 mm.
[0055] As a preferred embodiment, the injection molding temperature is 260°C to 290°C.
[0056] As a preferred implementation, the magnetic field orientation current is 40A to 60A.
[0057] The third aspect of the present invention is to provide a magnetic product, comprising the ferrite plastic magnetic material with a high powder filling rate as described in the first aspect, or prepared and processed based on the ferrite plastic magnetic material with a high powder filling rate as described in the first aspect.
[0058] In some optional embodiments, the magnetic product includes a micro motor, or a variable frequency home appliance, office equipment, high-end automobile, etc. made based on the micro motor.
[0059] Example 1
[0060] (1) Prepare the following raw materials: PA6 (RADILON S22, Radici Engineering Plastics Co., Ltd.) 85 kg, erucamide 8 kg, EBS 4 kg, SEBS-g-MAH (Kraton RP6670) 2.5 kg, and calcium montanate (Clariant CAV102) 0.5 kg.
[0061] First, put the PA6 into the oven and dry it at 100℃ for 16h. Then mix the above-configured raw materials in a high-speed mixer for 5min to obtain a PA6 mixture; extrusion granulation is carried out in a twin-screw extruder, and the extruder feed port temperature is set to 190℃, the discharge port temperature is set to 215℃, the speed is set to 30% Max, the pressure is set to 1.0MPA, and the torque is set to 35%; after the material is discharged from the die and cooled by a drag chain, it is pelletized using a pelletizer to obtain a modified PA6 with a particle size of 2.8mm.
[0062] (2) Prepare the following raw materials: 1000 kg ferrite powder (Beikuang Magnetic Material, BMXF-7), 10 kg alcohol, 10 kg coupling agent (Si-900), 98 kg modified PA6, 0.2 kg antioxidant 168, and 0.2 kg antioxidant 1098.
[0063] Mix the alcohol and the coupling agent evenly; pour the ferrite magnetic powder into a high-speed mixer, add the mixture of alcohol and the coupling agent, and stir the high-speed mixer for 5 minutes to discharge the material; put the material into an oven after discharge, and dry it at 100°C for 2 hours to evaporate all the alcohol, thereby obtaining a primary mixed magnetic powder treated with the coupling agent.
[0064] The primary mixed magnetic powder and the other raw materials configured above are poured into a high-speed mixer, stirred for 5 minutes, and discharged to obtain the secondary mixed magnetic powder. The secondary mixed magnetic powder is extruded and mixed by a twin-screw extruder, and the extrusion temperature of the extruder is set to be controlled at 240°C; after extrusion, it is cooled, and then a pelletizer is used to obtain a ferrite / modified PA6 injection molding compound.
[0065] (3) The ferrite / modified PA6 injection molding material is injection molded on an injection molding machine with a magnetic field orientation device mold; the injection molding temperature is controlled at 275° C., the injection molding pressure is 70%, the injection molding speed is 70%, and the orientation current is 60A; and a plastic magnetic product with a diameter of 40 mm*28 mm is obtained.
[0066] Example 2
[0067] It is basically the same as Example 1, except that:
[0068] In the raw material preparation of step (2): the amount of modified PA6 is replaced with 86 kg.
[0069] Example 3
[0070] It is basically the same as Example 1, except that:
[0071] In the raw material preparation of step (2): the amount of modified PA6 is replaced with 63 kg.
[0072] Example 4
[0073] It is basically the same as Example 1, except that:
[0074] In the raw material preparation of step (1): erucamide is replaced by oleamide; SEBS-g-MAH is replaced by POE-g-MAH (Xiamen Coase W1).
[0075] Example 5
[0076] It is basically the same as Example 1, except that:
[0077] In the raw material preparation of step (1): SEBS-g-MAH is replaced by POE-g-GMA (Shanghai Jiayirong SOG-02).
[0078] Comparative Example 1
[0079] It is basically the same as Example 1, except that:
[0080] The raw material preparation of step (2) is replaced as follows: 1000 kg ferrite powder (Beikuang Magnetic Material, BMXF-7), 10 kg alcohol, 10 kg coupling agent (Si-900), 68.1 kg PA6 (RADILON S22, Lantic Engineering Plastics Co., Ltd.), 19.6 kg PA6 (Ube 1013, Japan), 10.3 kg lubricant (TAF), 0.2 kg antioxidant 168, and 0.2 kg antioxidant 1098.
[0081] Comparative Example 2
[0082] It is basically the same as Example 1, except that:
[0083] The raw material preparation of step (2) is replaced as follows: 1000 kg ferrite powder (Beikuang Magnetic Material, BMXF-7), 10 kg alcohol, 10 kg coupling agent (Si-900), 60.5 kg PA6 (Randiqi Engineering Plastics Co., Ltd., RADILON S22), 15.2 kg PA6 (Xinhui Meida M2400), 10.3 kg lubricant (EBS), 0.2 kg antioxidant 168, and 0.2 kg antioxidant 1098.
[0084] Comparative Example 3
[0085] It is basically the same as Example 1, except that:
[0086] The raw material preparation of step (2) is replaced as follows: 1000 kg ferrite powder (Beikuang Magnetic Material, BMXF-7), 10 kg alcohol, 10 kg coupling agent (Si-900), 43.2 kg PA6 (Randiqi Engineering Plastics Co., Ltd., RADILON S22), 10.8 kg PA612 (Ube 7024B, Japan), 9.0 kg lubricant (silicone powder), 0.2 kg antioxidant 168, and 0.2 kg antioxidant 1098.
[0087] Comparative Example 4
[0088] It is basically the same as Example 1, except that:
[0089] The raw material preparation of step (1) was replaced with: PA6 (RADILON S22, Radici Engineering Plastics Co., Ltd.) 85 kg, erucamide 8 kg, EBS 4 kg, and calcium montanate (Clariant CAV102) 0.5 kg.
[0090] Comparative Example 5
[0091] It is basically the same as Example 1, except that:
[0092] PA6 (RADILON S22, Radici Engineering Plastics Co., Ltd.) 85kg, erucamide 8kg, EBS 4kg, SEBS-g-MAH (Kraton RP6670) 2.5kg.
[0093] The magnetic properties and mechanical properties of the plastic magnet products prepared in each embodiment and comparative example were tested; specifically, the magnetic properties were measured using the DMT-1 magnetometer of the Chinese Academy of Metrology, and the IZOD impact strength of the injection molded magnets was tested according to ASTM-D256 using the XWW-20KN electronic universal testing machine of Chengde Dahua Testing Co., Ltd., and the tensile strength of the injection molded magnets was tested according to ASTM-D638; the flowability was tested using the F-F01 melt index meter produced by Toyo Seiki Co., Ltd. of Japan, and the melt index MFR of the injection molded pellets at a temperature of 270°C with a load of 10 kg was tested according to the ASTMD1238 standard. The test results are shown in Table 1 below.
[0094] Table 1
[0095]
[0096] Based on the results in Table 1, it can be seen that each embodiment has good performance in fluidity, magnetic properties and mechanical properties. Comparative Examples 1 and 2 use a combination of two conventional PA6 and medium viscosity PA6 (increase tensile strength) and a conventional lubricant component, and Comparative Example 3 uses a combination of two conventional PA6 and PA612 (increase impact strength) and a conventional lubricant component. Comparative Examples 4 and 5 lack the core compatibilizing component and nucleating component of the present invention, respectively. It can be seen that the comparative examples are significantly inferior to the embodiments in one or two properties.
[0097] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A ferrite plastic magnetic material with high powder filling rate, characterized in that: The ferrite plastic magnetic material comprises ferrite magnetic powder, PA6 and an additive; the additive comprises a first lubricating component, a second lubricating component, a compatible component and a nucleating component; Wherein, the mass proportion of the ferrite magnetic powder is ≥91%; The first lubricating component includes at least one of erucamide or oleamide; The second lubricating component includes ethylene bisstearamide; The compatible component comprises at least one of hydrogenated styrene-butadiene block copolymer grafted with maleic anhydride, hydrogenated styrene-butadiene block copolymer grafted with glycidyl methacrylate, polyolefin elastomer grafted with maleic anhydride, and polyolefin elastomer grafted with glycidyl methacrylate; The nucleating component includes calcium montanate.
2. The ferrite plastic magnetic material with high powder filling rate according to claim 1, characterized in that: The PA6 includes one or more of the following features: (a) The molecular weight of the PA6 is 15,000 to 30,000; (b) the relative viscosity of the PA6 is 1.80 to 2.45; (c) the melting point of the PA6 is 210°C to 230°C, and the heat deformation temperature of the PA6 is 50°C to 80°C; (d) The density of PA6 is 1.10 g / cm 3 ~1.18g / cm 3 , the moisture content of PA6 is ≤0.15%.
3. The ferrite plastic magnetic material with high powder filling rate according to claim 1, characterized in that: The molecular weight of the compatible component is 70,000 to 150,000; Preferably, the compatibilizing component comprises hydrogenated styrene-butadiene block copolymer grafted with maleic anhydride.
4. The ferrite plastic magnetic material with high powder filling rate according to claim 1, characterized in that: The ferrite plastic magnetic material comprises the following components by mass: 1000 parts of ferrite magnetic powder, 80-90 parts of PA6, 5-15 parts of a first lubricating component, 2-8 parts of a second lubricating component, 1-5 parts of a compatible component and 0.1-2 parts of a nucleating component.
5. The ferrite plastic magnetic material with high powder filling rate according to claim 1, characterized in that: The ferrite plastic magnetic material also includes 0.1 to 1 parts of antioxidant and / or 0.1 to 2 parts of coupling agent by mass; Preferably, the antioxidant includes at least one of a hindered phenol antioxidant, a phosphite antioxidant or an aromatic amine antioxidant; preferably, the coupling agent includes at least one of a silane coupling agent or a titanate coupling agent.
6. The ferrite plastic magnetic material with high powder filling rate according to claim 1, characterized in that: In the ferrite plastic magnetic material, the mass proportion of the ferrite magnetic powder is 91% to 94%.
7. The ferrite plastic magnetic material with high powder filling rate according to claim 1, characterized in that: The magnetic properties of the ferrite plastic magnetic material include: B r ≥285mT,H cj ≥220kA / m,(BH) max ≥16.0kJ / m 3 ,MFR≥ 120g / 10min.
8. The method for preparing the ferrite plastic magnetic material according to any one of claims 1 to 7, characterized in that: The steps include: The ferrite powder, PA6 and additives are mixed until uniform, and then extruded into granules, and after cooling, injection molded in a magnetic field to obtain a plastic magnetic material.
9. The method for preparing ferrite plastic magnetic material according to claim 8, characterized in that: Before the preparation method, the PA6 is dried; Preferably, the temperature of the drying treatment is 80° C. to 120° C., and the time of the drying treatment is 12 h to 20 h.
10. A magnetic product, characterized in that: It comprises the ferrite plastic magnetic material as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Laminated film
JP1998157024A